Modelling and Implementation of Complex Systems Proceedings of the 5th International Symposium, MISC 2018, December 16-18, 2018, Laghouat, Algeria - Chikhi, Salim; Amine, Abdelmalek; Chaoui, Allaoua; Saidouni, Djamel Eddine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the fifth International Symposium on Modelling and Implementation of Complex Systems (MISC 2018). The event was held in Laghouat, Algeria, on December 16-18, 2018. The 25 papers gathered here have been selected from 109 submissions using a strict peer-review process, and address a range of topics concerning the theory and applications of networking and distributed computing, including: cloud computing and the IoT, metaheuristics and optimization, computational intelligence, software engineering and formal methods. .
Keywords: Computational intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Applied Dynamical Systems